Märgspaltning - matnyttigt om fragmentering - Stålberg,Karin (2025)
Fragmentation from the extraction of bone marrow for consumption is a common phenomenon in archaeological assemblages, because of the high fat content of bone marrow, it was an important source of sustenance in prehistory. From the perspective of marrow fracturing, analysis of these fragmented refuse materials gives insight into the general strategies for harvesting bone marrow. The fragmentation can cause several problems that affect our interpretation which shows the importance of contextual analysis. This study compares an early medieval town site in south Sweden with a pre-Christian iron-age farm site in the same area to show changes over time. A sample from this material, comprising 345 fragments with signs of marrow fracturing, was analysed to study what tools were used and how the animals might have been utilized. The general outline of the strategies found is presented, where much of the evidence points to a similar traditional agrarian subsistence with the exception of the horse that ceased to be used for consumption at sites influenced by Christianity. The shift from using a mixed set of tools in the iron age for marrow fracturing to a more heavy reliance on the axe during medieval times is discussed and exemplified.
Keywords: Marrow; fat; bone fragmentation; taphonomy; tools; utility; medieval; iron age; cooking; ben; märgspaltning; märg; märgklyvning; fragmentering; tafonomi; redskap; medeltid; järnålder